Target selection: Invasion, mapping and cell choice. - Holt, C.E.; Harris, W.A. (Current Opinion in Neurobiology, 1998)
Recent research has shown that changes in the concentration of particular molecules lead axons to invade their target, and that concentration changes in other molecules at the borders of the target prevent axons from leaving the target area. After invasion, topographic and lamina-specific cues guide axons to the correct location within the target field. At the level of a single cell or part of a cell, the evidence raises the possibility that axon targeting might be a combinatorial affair whereby specific axons compare the relative concentrations of several molecules on the surface of postsynaptic cells in order to choose a particular target. Both proteins and carbohydrates of various classes play major roles in these processes.